The disturbed outer Milky Way disc. Issue 4 (15th September 2022) - McMillan, Paul J; Petersson, Jonathan; Tepper-Garcia, Thor; Bland-Hawthorn, Joss; Antoja, Teresa; Chemin, Laurent; Figueras, Francesca; Khanna, Shourya; Kordopatis, Georges; Ramos, Pau; Romero-Gómez, Merce; Seabroke, George
ABSTRACT: The outer parts of the Milky Way's disc are significantly out of equilibrium. Using only distances and proper motions of stars from Gaia 's Early Data Release 3, in the range | b | < 10°, 130° < ℓ < 230°, we show that for stars in the disc between around 10 and $14\, kpc$ from the Galactic centre, vertical velocity is strongly dependent on the angular momentum, azimuth, and position above or below the Galactic plane. We further show how this behaviour translates into a bimodality in the velocity distribution of stars in the outer Milky Way disc. We use an N -body model of an impulse-like interaction of the Milky Way disc with a perturber similar to the Sagittarius dwarf to demonstrate that this mechanism can generate a similar disturbance. It has already been shown that this interaction can produce a phase spiral similar to that seen in the Solar neighbourhood. We argue that the details of this substructure in the outer galaxy will be highly sensitive to the timing of the perturbation or the gravitational potential of the Galaxy, and therefore may be key to disentangling the history and structure of the Milky Way.